Analysis of visual representations in middle school U.S. History texts. Issue 2 (3rd April 2018) - King-Sears, Margaret E.; Berkeley, Sheri; Arditi, Orit; Daley, Hyle L.; Hott, Brittany L.; Larsen, Anna L.
Abstract: This study analyzed three types of visual representations (graphs, maps, & graphic organizers) in the most widely used eighth-grade U.S. History textbooks. The analyses included how each visual was constructed and used within the context of text narrative. Purposeful sampling techniques were used to select a representative sample of varied topics addressed in all textbooks. Findings indicate that graphic organizers and maps were used more frequently across texts than graphs. Although most visuals were constructed well, few texts explicitly or implicitly connected the visuals to texts' narrative, which has literacy implications for students' comprehension. Other strengths and areas of need are identified. For areas of need, implications for pedagogies to enhance students' comprehension of and connections with the visuals themselves are described.